Pengembangan Media Pembelajaran Kurikulum 2013 di Kelas IV Tema 9 Subtema 1 - Indri Anugraheni; Firosalia Kristin (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2018)
The purpose of this study is to develop 2013 Curriculum-based learning media. This type of research is development research. The data analysis technique used in this study is to perform instrument validation in accordance with the criteria of the learning instrument validation indicator and then describe the results of data analysis. The product produced from this development research is 2013 Curriculum-Based Learning Media. The results of the analysis shows that the learning media developed in the sub-theme